Refugia Ditinjau Dari Konsep Gulma Pengganggu Dan Upaya Konservasi Musuh Alami - Asyik Nur Allifah AF; Rosmawati Rosmawati; Zamrin Jamdin (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Weed is a part of OPT (Plant Disturbing Organism) besides plant pests and diseases. Weeds cause damage slowly, due to competition with cultivated plants to obtain nutrients, water, light, CO2 and growing space. Weeds are harmful and disturbing so humans try to control them. From various aspects of life both health, aesthetics, environment and the field of farming, weeds can interfere with natural habitat and beauty. Weeds are always considered as exotic plants or migrants that are invasive and potentially disrupt the local environment. However, not all weeds play a negative and potentially disturbing role. Weeds are also able to provide a comfortable habitat for the development of natural enemies in the agrosecosystem. Refugia is a weed plant area that can provide shelter, food sources or other resources for natural enemies such as predators and parasitoid. Efforts to conserve natural enemies using refugia are one alternative to controlling plant pest organisms such as pests. Keywords: Refugia, Weeds, Conservation, Natural Enemies